Preparation method of micron-sized hexagonal iron / graphene composite wave-absorbing material
The hexagonal iron/graphene composite addresses graphene's impedance mismatch by enhancing impedance matching and magnetic permeability, achieving superior electromagnetic wave absorption with a maximum -67.95dB absorption and 6.03GHz bandwidth.
Patent Information
- Application Number
- CN202411253847.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
Graphene's high electrical conductivity leads to impedance mismatch and weak attenuation capability, limiting its broadband and strong absorption performance due to single dielectric loss mechanism.
A micron-scale hexagonal iron/graphene composite is prepared using a hydrothermal method and thermal reduction, adjusting the dielectric constant with anisotropic hexagonal iron to enhance impedance matching and magnetic permeability, forming a three-dimensional conductive network for enhanced electromagnetic wave absorption.
The composite material achieves good wave absorption performance with a maximum absorption intensity of -67.95dB and a bandwidth of 6.03GHz, overcoming impedance mismatch and improving conductivity and dielectric properties.
Smart Images

Figure CN119119957A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of electromagnetic wave absorbing materials, and in particular to a method for preparing a micron-scale hexagonal iron / graphene composite absorbing material. Background Art
[0002] With the rapid development of communication technology, electromagnetic pollution has become increasingly serious due to the widespread application of electronic equipment in military and civilian fields. Electromagnetic radiation not only interferes with the normal operation of equipment, but also damages the environment and threatens human health. Therefore, the design and preparation of electromagnetic wave absorbing materials are of great significance in the civilian and military fields. Carbon materials (such as carbon nanotubes, graphene, carbon fibers, carbon black, etc.) have the characteristics of low density, high specific surface area and excellent conductivity, which can meet the requirements of "thin, light, wide and strong" and have broad application prospects in the field of electromagnetic protection.
[0003] Compared with other traditional carbon materials, graphene has a unique two-dimensional structure, high thermal conductivity, high carrier mobility, low resistivity, large specific surface area and excellent chemical stability, which has attracted widespread attention from researchers. However, due to the high electron mobility, the high conductivity of graphene can lead to strong reflection and impedance mismatch. In addition, the van der Waals force effect of graphene sheets makes it easy for the sheets to agglomerate and pile up, which also seriously damages the overall absorption performance. More importantly, the single dielectric loss mechanism makes it difficult to achieve broadband and strong absorption. Summary of the invention
[0004] The present invention provides a method for preparing a micron-scale hexagonal iron / graphene composite absorbing material in order to solve the key technical problem that graphene has impedance mismatch and weak attenuation capability due to its high electrical conductivity and high dielectric properties.
[0005] The composite of graphene and magnetic materials can adjust the dielectric constant of the material, and the presence of magnetic materials can increase the magnetic permeability, which not only improves impedance matching but also has electromagnetic synergistic loss capability, thereby obtaining good wave absorption performance. Magnetic materials with anisotropic structures can break through the Snoek limit, thereby greatly improving the wave absorption capability.
[0006] The present invention adopts hydrothermal method and thermal reduction method to prepare micron-sized hexagonal iron / graphene (Fe / RGO) composite material. The dielectric constant of RGO is optimized by adjusting the content of anisotropic hexagonal iron, and the balance between attenuation capability and impedance matching is achieved. The polar sites and heterogeneous interfaces of Fe and RGO enhance dipole polarization and interface polarization. The three-dimensional conductive network structure contributes to multiple reflections and conduction losses of incident electromagnetic waves. In addition, the natural resonance, exchange resonance, and eddy current loss caused by the anisotropic hexagonal iron further enhance the magnetic loss. The dielectric-magnetic loss mechanism and good impedance matching jointly promote the electromagnetic wave energy loss.
[0007] The invention uses metal cations as precursors and cetyltrimethylammonium bromide as a surfactant to induce the generation of anisotropic morphology, mixes graphene oxide with the metal cations and the surfactant, and performs a hydrothermal reaction and a freeze-drying process, followed by a heat treatment in a reducing gas atmosphere to prepare an iron / graphene composite material.
[0008] A method for preparing a micron-sized hexagonal iron / graphene composite absorbing material is specifically carried out in the following steps:
[0009] Step 1: adding surfactant hexadecyltrimethylammonium bromide and potassium hydroxide into deionized water and stirring them magnetically until they are completely dissolved to obtain a mixed solution containing the surfactant;
[0010] Step 2: Place ferric nitrate nonahydrate into deionized water and stir magnetically until it is completely dissolved to obtain a ferric nitrate solution;
[0011] Step 3, adding the mixed solution containing the surfactant obtained in step 1 to the ferric nitrate solution obtained in step 2, and magnetically stirring to obtain a uniformly dispersed mixed solution of the metal salt containing the surfactant;
[0012] Step 4: dispersing graphene oxide powder into deionized water and stirring with ultrasonic waves to obtain a graphene oxide solution; the concentration of the graphene oxide solution is 6 to 10 mg / mL;
[0013] Step 5: adding the graphene oxide solution obtained in step 4 to the metal salt mixed solution containing a surfactant obtained in step 3, and magnetically stirring to obtain a uniformly dispersed graphene oxide mixed solution containing a surfactant and a metal salt;
[0014] Step 6: Transfer the graphene oxide mixed solution containing surfactant and metal salt obtained in step 5 to a Teflon high-pressure reactor, put it into a vacuum drying oven, and carry out a hydrothermal reaction at a temperature of 200-250° C. for a reaction time of 1-3 hours. After the reaction, cool it to room temperature, wash it repeatedly with deionized water and ethanol; then put it into a freeze dryer for freeze drying; and then put it into a tubular furnace for reduction under a hydrogen atmosphere to obtain a black solid powder, which is the micron-sized hexagonal iron / graphene composite absorbing material, and the preparation is completed.
[0015] The beneficial effects of the present invention are:
[0016] 1. The Fe / RGO composite wave-absorbing material of the present invention has simple process, high safety, low cost, and can be mass-produced.
[0017] Second, the introduction of anisotropic hexagonal iron has a significant regulatory effect on the dielectric properties of graphene. By controlling the mass ratio of Fe and RGO, the conductivity and complex dielectric constant of RGO are significantly reduced, which can effectively improve impedance matching.
[0018] 3. The micron-sized hexagonal iron / graphene composite absorber prepared by the method of the present invention, the hexagonal iron is anchored on the RGO sheets and connected to each other to form a mesh structure, which helps to form a conductive network and multiple interfaces between Fe and RGO, and promotes conductivity loss and interface polarization. The abundant defects and polar functional groups in the Fe / RGO composite material can serve as polarization centers to induce dipole polarization. In addition, the natural resonance, exchange resonance, and eddy current loss contributed by the anisotropic hexagonal iron further enhance the magnetic loss, thereby synergistically promoting the attenuation of electromagnetic wave energy.
[0019] 4. The micron-sized hexagonal iron / graphene composite absorbing material prepared by the method of the present invention has significant absorbing performance. When the filling amount is 10wt%, the maximum absorption intensity is -67.95dB, and the effective absorption bandwidth is 6.03GHz, which has good application prospects.
[0020] The hexagonal iron / graphene composite wave absorbing material prepared by the method of the present invention is applied to the field of electromagnetic wave absorbing materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 XRD spectra of the micron-sized hexagonal iron / graphene composite material (Fe / RGO) and the RGO comparison sample obtained in Example 1;
[0022] Figure 2 The SEM images of the micron-sized hexagonal iron / graphene composite material (Fe / RGO) obtained in Example 1 at different magnifications, wherein the scale of Figure a is 5 μm and the scale of Figure b is 1 μm;
[0023] Figure 3 The microscopic images of the micron-sized hexagonal iron / graphene composite material (Fe / RGO) obtained in Example 1, wherein (a) is a TEM image, (b) is a HRTEM image, and (c) is a SAED image;
[0024] Figure 4 The Raman images of the micron-sized hexagonal iron / graphene composite material (Fe / RGO) and the RGO comparison sample obtained in Example 1;
[0025] Figure 5 The hysteresis loop diagram of the micron-sized hexagonal iron / graphene composite material (Fe / RGO) and the RGO comparison sample obtained in Example 1;
[0026] Figure 6It is the electromagnetic parameter curve of RGO comparison sample;
[0027] Figure 7 is a curve diagram of the wave absorption performance of the RGO comparison sample, curve 1 represents 1.0mm thickness, curve 2 represents 1.26mm thickness, curve 3 represents 1.5mm thickness, curve 4 represents 2.0mm thickness, curve 5 represents 2.5mm thickness, curve 6 represents 3.0mm thickness, curve 7 represents 3.5mm thickness, and curve 8 represents 4.0mm thickness;
[0028] Figure 8 This is a graph of electromagnetic parameters of the micron-sized hexagonal iron / graphene composite material (Fe / RGO) obtained in Example 1;
[0029] Fig. 9 This is a curve diagram of the wave absorption performance of the micron-sized hexagonal iron / graphene composite material (Fe / RGO) obtained in Example 1, where curve 1 represents a thickness of 1.0 mm, curve 2 represents a thickness of 1.5 mm, curve 3 represents a thickness of 2.0 mm, curve 4 represents a thickness of 2.5 mm, curve 5 represents a thickness of 3.0 mm, curve 6 represents a thickness of 3.47 mm, curve 7 represents a thickness of 3.5 mm, and curve 8 represents a thickness of 4.0 mm. DETAILED DESCRIPTION
[0030] Specific implementation method 1: This implementation method is a method for preparing a micron-sized hexagonal iron / graphene composite absorbing material, which is specifically carried out in the following steps:
[0031] Step 1: adding surfactant hexadecyltrimethylammonium bromide and potassium hydroxide into deionized water and stirring them magnetically until they are completely dissolved to obtain a mixed solution containing the surfactant;
[0032] Step 2: Place ferric nitrate nonahydrate into deionized water and stir magnetically until it is completely dissolved to obtain a ferric nitrate solution;
[0033] Step 3, adding the mixed solution containing the surfactant obtained in step 1 to the ferric nitrate solution obtained in step 2, and magnetically stirring to obtain a uniformly dispersed mixed solution of the metal salt containing the surfactant;
[0034] Step 4: dispersing graphene oxide powder into deionized water and stirring with ultrasonic waves to obtain a graphene oxide solution; the concentration of the graphene oxide solution is 6 to 10 mg / mL;
[0035] Step 5: adding the graphene oxide solution obtained in step 4 to the metal salt mixed solution containing a surfactant obtained in step 3, and magnetically stirring to obtain a uniformly dispersed graphene oxide mixed solution containing a surfactant and a metal salt;
[0036] Step 6: Transfer the graphene oxide mixed solution containing surfactant and metal salt obtained in step 5 to a Teflon high-pressure reactor, put it into a vacuum drying oven, and carry out a hydrothermal reaction at a temperature of 200-250° C. for a reaction time of 1-3 hours. After the reaction, cool it to room temperature, wash it repeatedly with deionized water and ethanol; then put it into a freeze dryer for freeze drying; and then put it into a tubular furnace for reduction under a hydrogen atmosphere to obtain a black solid powder, which is the micron-sized hexagonal iron / graphene composite absorbing material, and the preparation is completed.
[0037] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the mass volume ratio of hexadecyltrimethylammonium bromide, potassium hydroxide and deionized water in step 1 is 1g:15g:10mL. Others are the same as specific embodiment 1.
[0038] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that: the magnetic stirring time in step 1 is 2 to 4 hours, and the stirring speed is 250 to 450 r / min. The rest is the same as specific implementation method 1 or 2.
[0039] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the concentration of the ferric nitrate solution in step 2 is 100-300 mg / mL. Other aspects are the same as those of specific embodiments 1 to 3.
[0040] Specific implementation mode 5: This implementation mode is different from specific implementation modes 1 to 4 in that the magnetic stirring time in step 2 is 1 to 2 hours and the stirring speed is 250 to 450 r / min. The rest is the same as specific implementation modes 1 to 4.
[0041] Specific implementation method 6: This implementation method is different from specific implementation methods 1 to 5 in that the magnetic stirring time in step 3 is 3 to 6 hours and the stirring speed is 250 to 450 r / min. The rest is the same as specific implementation methods 1 to 5.
[0042] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: in the ultrasonic stirring process described in step 4, the ultrasonic power is 500-800W, the time is 1-2h, the magnetic stirring is 1-3h, and the stirring speed is 250-450r / min. Others are the same as specific embodiments 1 to 6.
[0043] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the magnetic stirring time in step 5 is 2 to 5 hours and the stirring speed is 250 to 450 r / min. The rest is the same as specific embodiments 1 to 7.
[0044] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the freeze-drying process in step 6 is carried out at a temperature of -50 to -60°C, for 24 to 48 hours, and at a pressure of 0.1 to 1 Pa. The rest is the same as specific embodiments 1 to 8.
[0045] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the reduction temperature in step 6 is 300-400°C, the heating rate is 1-5°C / min, and the holding time is 1-3h. The rest is the same as specific embodiments 1 to 9.
[0046] The content of the present invention is not limited to the content of the above-mentioned embodiments. The combination of one or several specific embodiments can also achieve the purpose of the invention.
[0047] Embodiment 1:
[0048] The present embodiment provides a method for preparing a micron-sized hexagonal iron / graphene composite absorbing material (Fe / RGO), which is specifically carried out in the following steps:
[0049] Step 1: Put 1g of surfactant hexadecyltrimethylammonium bromide and 15g of potassium hydroxide into 10mL of deionized water and stir magnetically for 3h at a stirring speed of 350r / min to obtain a mixed solution containing a surfactant;
[0050] Step 2: Place 2 g of ferric nitrate nonahydrate into 10 mL of deionized water and stir magnetically for 1 h at a stirring speed of 350 r / min to obtain a ferric nitrate solution with a concentration of 200 mg / mL;
[0051] Step 3: Add the mixed solution containing the surfactant obtained in step 1 to the ferric nitrate solution obtained in step 2, and stir magnetically for 4 hours at a stirring speed of 350 r / min to obtain a uniformly dispersed mixed solution of metal salt containing the surfactant;
[0052] Step 4: Disperse 1 g of graphene oxide powder in 125 mL of deionized water for 1 h at a power of 600 W, a magnetic stirring time of 2 h, and a stirring speed of 350 r / min to obtain a uniformly dispersed graphene oxide solution with a concentration of 8 mg / mL;
[0053] Step 5: adding the graphene oxide solution obtained in step 4 to the metal salt mixed solution containing a surfactant obtained in step 3, and stirring with magnetic force for 4 hours at a stirring speed of 400 r / min to obtain a uniformly dispersed graphene oxide mixed solution containing a surfactant and a metal salt;
[0054] Step 6. Transfer the graphene oxide mixed solution containing surfactants and metal salts obtained in step 5 to a Teflon high-pressure reactor, place it in a vacuum drying oven, and carry out a hydrothermal reaction at a temperature of 240°C for a reaction time of 2 hours. After the reaction is completed, cool it to room temperature and wash it repeatedly with deionized water and ethanol; then place it in a freeze dryer for freeze drying at a temperature of -58°C for 36 hours and a pressure of 0.3Pa; then place it in a tubular furnace for reduction under a hydrogen atmosphere at a temperature of 350°C, a heating rate of 5°C / min, and a holding time of 2 hours to obtain a black solid powder, which is the micron-sized hexagonal iron / graphene composite absorbing material (Fe / RGO), and the preparation is completed.
[0055] Preparation of test samples:
[0056] The micron-sized hexagonal iron / graphene composite absorbing material (Fe / RGO) prepared in step 6 of Example 1 was placed in paraffin at a mass ratio of 10%, heated to 90°C, and kept warm for 0.5h. The sample was placed in a mold to finally obtain a coaxial ring with an outer diameter of 7mm, an inner diameter of 3.04mm, and a thickness of 2mm.
[0057] RGO comparison sample:
[0058] 125 mL of graphene oxide solution obtained in step 4 of Example 1 was placed in a refrigerator and frozen into a solid, and then placed in a freeze dryer for freeze drying for 36 hours at a temperature of -58°C and a pressure of 0.3 Pa; then placed in a tubular furnace for reduction under a hydrogen atmosphere at a temperature of 350°C, a heating rate of 5°C / min, and a holding time of 2 hours to obtain a black solid powder, thereby obtaining an RGO comparison sample.
[0059] The RGO control sample was prepared as the same test sample as in Example 1.
[0060] The micron-sized hexagonal iron / graphene composite absorbing material (Fe / RGO) prepared in Example 1 was tested against a RGO comparison sample.
[0061] Figure 1 The XRD spectra of the micron-sized hexagonal iron / graphene composite material (Fe / RGO) and the RGO comparison sample obtained in Example 1. It can be seen from the figure that the sample Fe / RGO has the "mantou peak" of RGO, and at the same time, it shows three typical strong peaks of Fe at the positions of 44.73°, 65.04°, and 82.38°, which correspond to the (110), (200), and (221) crystal planes, respectively.
[0062] Figure 2The SEM images of the micron-sized hexagonal iron / graphene composite material (Fe / RGO) obtained in Example 1 at different magnifications show that the hexagonal iron is evenly dispersed on the RGO sheet, with a size of about 2 μm in width and about 100 nm in thickness.
[0063] Figure 3 The microscopic images of the micron-scale hexagonal iron / graphene composite material (Fe / RGO) obtained in Example 1, wherein (a) is a TEM image, (b) is a HRTEM image, and (c) is a SAED image. It can be seen from the figure that the Fe (110) plane corresponds to a lattice fringe distance of 0.2 nm. Ordered diffraction spots can be seen in the selected area electron diffraction (SAED), indicating that the hexagonal Fe is a single crystal structure.
[0064] Figure 4 The Raman graph of the micron-scale hexagonal iron / graphene composite material (Fe / RGO) obtained in Example 1 and the RGO comparison sample. The D and G peaks represent defects and graphitized carbon, respectively. It can be seen from the figure that with the introduction of Fe, I D / I G The value of increases from 0.89 to 0.98, indicating that the introduction of Fe leads to an increase in defects in RGO, which can act as polarization centers to induce dipole polarization.
[0065] Figure 5 The hysteresis loop diagram of the micron-scale hexagonal iron / graphene composite material (Fe / RGO) obtained in Example 1 and the RGO comparison sample, the Fe / RGO composite material has strong magnetic properties, and its saturation magnetization intensity is about 77.39emu / g, while RGO is a carbon material with a saturation magnetization intensity of 0 and no magnetism.
[0066] Figure 6 The electromagnetic parameter curve of the RGO comparison sample shows that the real and imaginary parts of the dielectric constant of graphene decrease with the increase of frequency, and the dielectric dispersion characteristics are obvious. Due to the high conductivity, the imaginary part is significantly higher than the real part, which will lead to impedance mismatch. The real and imaginary parts of the magnetic permeability are 1 and 0 respectively, proving that there is no magnetic loss.
[0067] Figure 7 This is the wave absorption performance curve of the RGO comparison sample. Curve 1 represents the thickness of 1.0mm, curve 2 represents the thickness of 1.26mm, curve 3 represents the thickness of 1.5mm, curve 4 represents the thickness of 2.0mm, curve 5 represents the thickness of 2.5mm, curve 6 represents the thickness of 3.0mm, curve 7 represents the thickness of 3.5mm, and curve 8 represents the thickness of 4.0mm. The wave absorption performance is poor at the thickness of 1 to 4.0mm, and the reflection loss values are all greater than -10dB.
[0068] Figure 8This is a graph of electromagnetic parameters of the micron-sized hexagonal iron / graphene composite material (Fe / RGO) obtained in Example 1. It can be seen from the figure that the real and imaginary parts of the dielectric constant of Fe / RGO both show a downward trend with increasing frequency, and the dielectric dispersion is obvious. The dielectric parameters fall within an appropriate range, which is conducive to impedance matching. In addition, the real and imaginary parts of the magnetic permeability are 1.15-1 and 0.15-0.1 respectively, and iron also plays a magnetic loss mechanism.
[0069] Fig. 9 The wave absorption performance curve of the micron-scale hexagonal iron / graphene composite material (Fe / RGO) obtained in Example 1, curve 1 represents 1.0mm thickness, curve 2 represents 1.5mm thickness, curve 3 represents 2.0mm thickness, curve 4 represents 2.5mm thickness, curve 5 represents 3.0mm thickness, curve 6 represents 3.47mm thickness, curve 7 represents 3.5mm thickness, and curve 8 represents 4.0mm thickness. It can be seen from the figure that Fe / RGO exhibits excellent wave absorption performance. When the thickness is 3.47mm, the maximum reflection loss is -67.95dB at a frequency of 8.48GHz; when the thickness is 2.5mm, the effective absorption bandwidth is 6.03GHz (10.82-16.85GHz).
Claims
1. A method for preparing a micron-sized hexagonal iron / graphene composite absorbing material, characterized in that The method is specifically carried out in the following steps: Step 1: adding surfactant hexadecyltrimethylammonium bromide and potassium hydroxide into deionized water and stirring them magnetically until they are completely dissolved to obtain a mixed solution containing the surfactant; Step 2: Place ferric nitrate nonahydrate into deionized water and stir magnetically until it is completely dissolved to obtain a ferric nitrate solution; Step 3, adding the mixed solution containing the surfactant obtained in step 1 to the ferric nitrate solution obtained in step 2, and magnetically stirring to obtain a uniformly dispersed mixed solution of the metal salt containing the surfactant; Step 4: dispersing graphene oxide powder into deionized water and stirring with ultrasonic waves to obtain a graphene oxide solution; the concentration of the graphene oxide solution is 6 to 10 mg / mL; Step 5: adding the graphene oxide solution obtained in step 4 to the metal salt mixed solution containing a surfactant obtained in step 3, and magnetically stirring to obtain a uniformly dispersed graphene oxide mixed solution containing a surfactant and a metal salt; Step 6: Transfer the graphene oxide mixed solution containing surfactant and metal salt obtained in step 5 to a Teflon high-pressure reactor, put it into a vacuum drying oven, and carry out a hydrothermal reaction at a temperature of 200-250° C. for a reaction time of 1-3 hours. After the reaction, cool it to room temperature, wash it repeatedly with deionized water and ethanol; then put it into a freeze dryer for freeze drying; and then put it into a tubular furnace for reduction under a hydrogen atmosphere to obtain a black solid powder, which is the micron-sized hexagonal iron / graphene composite absorbing material, and the preparation is completed.
2. The method for preparing a micron-sized hexagonal iron / graphene composite absorbing material according to claim 1, characterized in that The mass volume ratio of hexadecyltrimethylammonium bromide, potassium hydroxide and deionized water in step 1 is 1g:15g:10mL.
3. The method for preparing a micron-sized hexagonal iron / graphene composite absorbing material according to claim 1, characterized in that The magnetic stirring time in step 1 is 2 to 4 hours, and the stirring speed is 250 to 450 r / min.
4. The method for preparing a micron-sized hexagonal iron / graphene composite absorbing material according to claim 1, characterized in that The concentration of the ferric nitrate solution in step 2 is 100-300 mg / mL.
5. The method for preparing a micron-sized hexagonal iron / graphene composite absorbing material according to claim 1, characterized in that The magnetic stirring time in step 2 is 1 to 2 hours, and the stirring speed is 250 to 450 r / min.
6. The method for preparing a micron-sized hexagonal iron / graphene composite absorbing material according to claim 1, characterized in that The magnetic stirring time in step 3 is 3 to 6 hours, and the stirring speed is 250 to 450 r / min.
7. The method for preparing a micron-sized hexagonal iron / graphene composite absorbing material according to claim 1, characterized in that In the ultrasonic stirring process described in step 4, the ultrasonic power is 500-800 W, the time is 1-2 h, the magnetic stirring is 1-3 h, and the stirring speed is 250-450 r / min.
8. The method for preparing a micron-sized hexagonal iron / graphene composite absorbing material according to claim 1, characterized in that The magnetic stirring time in step 5 is 2 to 5 hours, and the stirring speed is 250 to 450 r / min.
9. The method for preparing a micron-sized hexagonal iron / graphene composite absorbing material according to claim 1, characterized in that The freeze-drying process in step 6 is performed at a temperature of -50 to -60°C, a time of 24 to 48 hours, and a pressure of 0.1 to 1 Pa.
10. The method for preparing a micron-sized hexagonal iron / graphene composite absorbing material according to claim 1, characterized in that The reduction temperature in step six is 300-400° C., the heating rate is 1-5° C. / min, and the insulation time is 1-3 h.
Citation Information
Patent Citations
Preparation method of graphene foam composite material supported with magnetic hollow nanospheres
CN110564365A
BiFeO3 / RGO composite wave-absorbing material and preparation method thereof
CN111171787A
Preparation method of graphene wave-absorbing material
CN111218256A
Nitrogen-doped graphene nickel ferrite composite wave-absorbing material and preparation method thereof
CN112375541A
Preparation method of graphene-loaded iron hexagonal nanosheet composite wave-absorbing material
CN115838585A
